The Relationship of Trust, Knowledge Transfer and the Person-Job and Person-Organization Fit as Moderating Effects - Wuryaningrat, Nikolas Fajar; Paulus, Ardianus Laurens; Rantung, Danny I.; Mandagi, Deske W. (Journal of Indonesian Economy and Business, 2024)
Introduction/Main Objectives: The study aims to assess the relationship between trust and knowledge transfer with PJ-fit and PO-fit as moderating variables. Background Problems: There are two divergent perspectives on knowledge transfer, and trust has been posited as a potential unifying factor that could mitigate these differences. Trust, in many studies, has been regarded as a crucial factor for knowledge transfer, although there is a blurred understanding between trust and distrust. PJ-fit and PO-fit are moderating variables in the relationship between trust and knowledge transfer. Novelty: Most PJ-fit and PO-fit studies discuss trust and knowledge transfer. This makes the constructs of PJ-fit and PO-fit, as the moderating variables between trust and knowledge transfer, a novelty in this research. Research Methods: This survey analyzed the employees in companies’ information and technology divisions and collected data from 271 participants. The data was analyzed with PLS-SEM 3.29. Finding/Results: The result revealed that trust significantly impacts knowledge transfer, with the relationship being strengthened by PJ-fit. Conclusion: The optimal fit of knowledge, skills, and abilities is essential in promoting the relationship between trust and knowledge transfer in organizations that require employees who are oriented toward high-tech abilities. Therefore, recruitment based on PJ-fit may be more suitable when looking for an employee with a strong emphasis on expertise.